The importance of collective anonymous data in the practice of the occupational physician: The lesson of Bernardino Ramazzini - Francesco CHIRICO; Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2023)
Occupational epidemiology principles are crucial for safeguarding workers’ health and safety, echoing the pioneering work of Bernardino Ramazzini, a key figure in occupational medicine. Ramazzini’s groundbreaking idea that the work environment contributes to disease underscores the need to examine working conditions for preventive health measures. The practice centers around annual health reports rooted in occupational epidemiology, akin to Ramazzini’s approach. Occupational physicians grasp the value of gathering and analyzing detailed health data from homogeneous worker groups to identify trends, allowing effective health protection strategies. In Italy, regulations mandate occupational physicians to present collective anonymous data during annual meetings, bolstering the role of accurate epidemiological principles in assessing risks and devising preventive measures. Ensuring confidentiality is essential, especially in the digital era and within smaller firms. The health surveillance cycle begins with a precise health protocol guiding diagnostic procedures, utilizing standardized data collection tools for reliability. The statistical analysis uncovers hidden patterns and targets specific risk groups, culminating in comprehensive annual health reports enriched with meticulous research. The statistical analysis of the collected data can highlight the effectiveness of implemented measures and can be shared with the scientific community through scientific publications. Occupational physicians, echoing Ramazzini, play a vital role in holistic risk assessment, utilizing detailed data analysis to identify issues and recommend interventions, thereby mitigating risk exposure and potential health threats.